PREDIÇÃO DA ÁREA DE DISTRIBUIÇÃO POTENCIAL DE UMA MOSCA-DA-FRUTA NÃO NATIVA NO BRASIL - Cristina de Paula Souza, Beatriz; Eduarda Martins Genoveski, Gabrielly; Bailly , Dayani; Fernando Esser , Luiz; Ré, Reginaldo; Flávia Batista Silva, Valéria (ANAIS DO ENIC, 2026)
-